Influence of annealing temperatures on the properties of low aspect-ratio TiO2 nanotube layers - Das, Sayantan; Zazpe, Raul; Přikryl, Jan; Knotek, Petr; Krbal, Miloš; Sopha, Hanna; Podzemná, Veronika; Macák, Jan M. (Elsevier, 2016)
The present work reports on the effect of thermal annealing on electrical, optical and structural properties of low aspect ratio self-organized TiO2 nanotube layers formed by anodization of Ti. The average inner diameter and length of the nanotubes was 100 nm and 1 µm, respectively. From the whole range of temperatures (300-600 °C), annealing at 400 oC leads to the formation of crystalline TiO2 nanotube layers with anatase structure offering best electrical and photo-electrochemical properties. Conducting atomic force microscopy studies have been explored for the first time to identify the annealing temperature of nanotube TiO2 layers with best electrical properties
Keywords: TiO2 nanotubes; anodization; annealing; anatase; rutile